PEMODELAN SILINDER BETON DENGAN KEKANGAN CFRP (CARBON FIBER REINFORCED POLYMER) - Cahyo, Bagas Dwi; Chairunnisa, Nursiah (Lambung Mangkurat University Press, 2020)
Confinement plays an important role in preventing cracking and premature shear failure, increasing the compressive strength and increasing the ductility of the element. One of the most efficient retrofitting methods is the reinforcement method with external restraints using high quality materials. Based on previous research, the use of external restraints using high quality materials can be in the form of steel wire mesh and wire rope restraints, and high-quality fiber such as CFRP (carbon fiber reinforced polymer). In this research, a study will be conducted to determine the effect of CFRP confinement reinforcement on a concrete cylinder that will be modeled with finite element software. The dimensions of the concrete cylinder used have a height of 300 mm and a diameter of 150 mm. The concrete cylinder is reinforced with CFRP with a thickness variation of 0.5 mm; 0.7 mm; and 1 mm respectively, namely SC.1.05-F, SC.1.07-F, SC.1.10-F. Then the samples with variations in the number of layers of 1 layer, 2 layers, and 3 layers respectively are SC.1.10-F, SC.2.10-F, SC.3.10-F. The last is the sample with a variety of full wrap installation configurations, CFRP with a width of 30 mm with a spacing of 50 mm, and CFRP with a width of 50 mm with a spacing of 50 mm, respectively, namely SC.1.10-F, SC.1.10-T3, and SC.1.10-T5. From the results of the analysis, it can be concluded that CFRP is able to increase the compressive strength of the sample with each increase in the compressive strength capacity of the test object compared to the Control Cylinder (SK). Based on the results of the analysis for all samples SC.1.10-T3, SC.1.10-T5, SC.1.05-F, SC.1.07-F, SC.1.10-F, SC.2.10-F and SC.3.10-F respectively of 10.79%; 25.24%; 33.66%; 39.50%; 49.85%; 78.21%, and 94.5%.